Perlindungan Hukum Bagi Pasien Terhadap Pelayanan Kesehatan Dan Perumahsakitan - Ari Tris Ochtia Sari (PSHPM Untag Semarang, 2025)
Health Law is one of the important laws that is currently growing in Indonesian society. Legal protection is an effort to protect human rights that have been harmed and provide a sense of security to witnesses and/or victims. Through the provision of restitution, compensation, medical services and legal assistance is a legal protection for victims of crimes that occur in the community. The form of legal protection for medical services in General Hospitals for patients in terms of patient protection, related to medical actions, health workers will convey an understanding to the patient first. The implementation of the application of medical services in General Hospitals is based on positive law that has been applied in Hospitals in fulfilling the rights of these patients which are carried out with full commitment and in accordance with the duties and functions in general in protecting the community. In this study, the author examines the extent to which legal protection for patients in medical services and medical implementation based on positive law is carried out in General Hospitals. This research method uses a Normative Juridical Approach with a descriptive analytical research nature.